Enhancing public participation in regional development : the case of Riyadh Regional Council - Alfaraj, Naif Faraj Saad (Curtin University, 2008)
This thesis examines public participation in regional development in Saudi Arabia at the local government level. The main objective of the study examines the current policies and practices of Riyadh Regional Council with regard to regional development, paying particular attention to the issue of public participation. Key decision-makers and decision locations are identified as focal points of policy development and implementation. The work begins from the premise that public participation is one of the key elements of effective regional policy that has so far been under-researched and consequently under-utilised in the Saudi Arabian context. The research opens by examining the national and cultural context of regional development in Saudi Arabia. It identifies and examines the relationship between policy development and the traditions and constitutional arrangements. These considerations are followed by an interrogation of the literature that reveals a range of concepts and perspectives on regional development and public participation. Of particular relevance to this study is the importance of the ‘institutional turn’ in regional development and the role of public participation in enhancing the functioning of those institutions associated with regional development. Saudi Arabia has an economy that is largely dependent on revenues generated from the export of crude and refined petrochemicals. This places Saudi Arabia in a category of nations that are liable to suffer from the ‘resource curse’. The literature suggests that avoiding this particular phenomenon is in part dependent on having robust institutions. This firmly connects the research problem to previous research and provides a sound rationale for the conduct of the study.Interpretivism is advanced as a suitable philosophical framework for the conduct of the research. It offers a methodological rationale for a case study investigation that draws on a range of qualitative data sources. Such an approach is especially useful for examining situations that are bound in time and space and can provide theoretical and practical insights that are useful in other contexts. This research presents new insights into how local government in Saudi Arabia can develop strategies for enhancing public participation in the creation of regional development policies and practices. There has been recent rapid economic development in Saudi Arabia that has influenced overall planning directions and development achievements and made it possible for the government to achieve systematic progress in long-term economic diversification into industrialisation, education, health, transport, and communication and social services. Even so, the Saudi Arabian government is concerned about increasing public participation in all areas. The formation of the regional councils in 1992 can be considered as a step towards public participation in the socio-economic development of their regions. However, the findings of this research demonstrate that there is a need for creating new policies and techniques to help regional councils in improving their performance to meet the needs of their citizens, and public participation is a key to achieving this end. To do this it is recommended that the councils should be granted executive and legislative authority to enable them to take adequate decisions and work together with citizens in ways that will increase their participation leading to enhanced transparency and accountability and effective regional development policy.Following the findings, a set of recommendations are provided to improve the role of Riyadh Regional Council in enhancing public participation in regional development. This thesis closes with suggestions and directions for future research with regard to the potential contribution to the public sector management literature. The findings of this research provide benefits for policy makers to correct, maintain, and eliminate any obstacles facing administrative policies and consequently provide a long-term strategy that could incrementally be implemented in stages throughout time. The research methods, ideas and insights developed here could also be adapted and applied to other nations facing similar issues.